2017
DOI: 10.4236/gep.2017.54002
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Trout (<i>Oncorhynchus mykiss</i>) Cage Culture: Preliminary Observations of Surface Sediment’s Chemical Parameters and Phosphorus Release in Gokcekaya Reservoir, Turkey

Abstract: This research was conducted in Gokcekaya Reservoir, which is located on the Sakarya River (Ankara, Turkey). Sediment samples were obtained before and after culture periods at a rainbow trout (Oncorhynchus mykiss) farm with a capacity of 950 t•y −1 . Total phosphorus (TP: 8.80 ± 0.50 and 9.10% ± 0.20%), total nitrogen (TN: 17.0 ± 0.20 and 17.05% ± 0.10%), organic matter (OM: 14.40 ± 0.40 and 14.60% ± 0.20%), redox potential (327.00 ± 0.08 and 170.00 ± 4.08 mV), water content (97.68 ± 0.28 and 96.38% ± 0.41%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As was verified in the sediment of the Rosário reservoir, Karakoca and Topcu [ 84 ] found that the strongest correlations of metals in the sediment of Lake Gokcekaya, Turkia occurred in the fish farming area.…”
Section: Resultsmentioning
confidence: 79%
“…As was verified in the sediment of the Rosário reservoir, Karakoca and Topcu [ 84 ] found that the strongest correlations of metals in the sediment of Lake Gokcekaya, Turkia occurred in the fish farming area.…”
Section: Resultsmentioning
confidence: 79%
“…However, high investment and slow growth are major challenges. Cage culture of rainbow trout is practiced widely in many other countries [11][12][13][14][15] There are several advantages of cage culture as it allows complete harvesting in the spring when the water temperature rises above their tolerance limits [7,16] .…”
Section: Introductionmentioning
confidence: 99%